Goal-setting with patients with multi-morbidity: Finding a way to achieve 'what really matters'. Issue 3 (March 2020) - Shiner, Alice; Player, Emily; Salter, Charlotte; Steel, Professor Nicholas
It can be a challenging task for GPs to find the best approach to providing care for patients with multiple medical conditions (multi-morbidity). Most care focuses on the management of single diseases; however, adopting a patient-centred focus may be better for patients with multi-morbidity. This is encouraged in recent health policy and guidance. However, it is not always clear how this should be put into practice. This article describes how GPs might use 'goal-setting' during consultations with patients with multi-morbidity, to help achieve more effective care that is better suited to patient's needs.